A Review of the Traditional Uses, Phytochemistry and Biological Activities of the Genus Santolina - Tundis, Rosa; Loizzo, Monica Rosa (Planta Medica, 2018)
The genus Santolina is a taxonomically complex group of plant species widely distributed in the Mediterranean flora and used in traditional medicine since ancient times for their biological properties, including antimicrobial, anti-inflammatory, antispasmodic, digestive, and analgesic activities. Phytochemical investigations of Santolina species have revealed the presence of terpenoids as the main bioactive constituents of the genus. Coumarins and flavonoids were also identified. This review deals, for the first time, with information on the traditional uses, chemical profile, and biological properties of plants of the genus Santolina in order to provide input for future research prospects.
Keywords: Santolina; Asteraceae; ethnobotany; phytochemicals; biological activities